The Short Stories of Anton Tchekov - Anton Chekhov; Robert N. Linscott (The Modern Library New York, 1932)
A collection of twenty-three of Chekhov's short stories: "A Day in the Country" "Old Age" "Kashtanka" "Enemies" "On the Way" "Vanka" "La Cigale" "Grief" "An Inadvertence" "The Black Monk" "The Kiss" "In Exile" "A Work of Art" "Dreams" "A Woman's Kingdom" "The Doctor" "A Trifling Occurence" "The Hollow" "After the Theatre" "The Runaway" "Vierochka" "The Steppe" "Rothchild's Fiddle" . Anton Chekhov
Keywords: Literature (3GdCOHs; General